Предмет: Математика,
автор: 123talshin
6(x+1)2+2(x-1)(x2+x+1)-2(x+1)3=26
Ответы
Автор ответа:
0
6х+7+2+2х-1×х12+12+6-2х+3=26
Автор ответа:
0
Раскрываем скобочки
12х+12+2х-2+х^3 + 1^3-6х-6=26
Сокращаем ( находим подобные слагаемые)
х^3-8х-3=26
Переносим -3 в левую часть
х^3-8х=29
Выносим х за скобку
х( х^2-8)=29
х=29 или х^2-8=28
х1= корень из 36=6
х2= минус корень из 36= -6
Похожие вопросы
Предмет: Математика,
автор: gerkinmishka
Предмет: Математика,
автор: polinaterekhova09
Предмет: География,
автор: nikaarh17
Предмет: Химия,
автор: Айсана
Предмет: Алгебра,
автор: Аня483